Socio-Economic Factors Influencing Forest Community Empowerment in Pacitan Regency - Riadi, Listiono; Eri Yusnita Arvianti; Budi Santosa (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2026)
This study aims to analyze the socio-economic factors that influence the empowerment of forest communities in Pacitan Regency, East Java. The study used a quantitative approach with an explanatory survey method of 350 respondents from five sub-districts (Donorojo, Pringkuku, Punung, Bandar, and Nawangan) selected through proportionate stratified random sampling. Data were analyzed using multiple linear regression to test the influence of nine independent variables (education level, income level, area of ​​cultivated land, access to capital, business experience, number of dependents, age, access to information and technology, and social and institutional capital) on the empowerment of forest communities. The results showed that simultaneously all variables had a significant effect on the empowerment of forest communities (F = 78.452; p < 0.05) with an R² value of 0.675, which means 67.5% of the variation in empowerment can be explained by the model. Partially, eight variables had a significant effect: education level, income level, area of ​​cultivated land, access to capital, business experience, number of dependents (negative effect), access to information and technology, and social and institutional capital. Only age was not significantly affected. The variables with the strongest partial correlations were access to information and technology (r=0.624) and social and institutional capital (r=0.618). This study recommends the need for comprehensive empowerment policies that include increased access to education, capital, technology, and strengthening LMDH institutions to sustainably improve the welfare of forest communities.